Faktor - Faktor Peranan Penggunaan Social Media E-Government: Studi Kasus Pemerintah Kota Prabumulih - Fajriyah Fajriyah; Darius Antoni; Muhammad Akbar (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2020)
With the development of the era of technology and information, it has also progressed very rapidly. Social media is one of the internet-based media which has an important role in the world of government to communicate with stakeholders in this global era. Increasingly sophisticated technology makes it easier for everyone to get the information they want so that thanks to the sophistication of information technology with the help of the internet, online media is increasingly easier to access, making online media one of the alternative media for public information that is effective in meeting the needs of human interaction. The largest social networks include Facebook and Twitter. The objective of this research is to measure how much the community responds as Prabumulih's follower in receiving the information provided through social media (Facebook, Twitter or Instagram). E-government can be interpreted in various ways because basically e-government can manifest itself in various forms and scope. The factors that influence the role of social media use in Prabumulih City Government are Technology Capacity, Interaction and Social media variables. In getting respondents, the writer used a questionnaire so that 200 respondents were obtained. The data from the questionnaire was managed using the SPSS program with the AMOS analysis model. From the Estimate value obtained from each variable is as follows, Technology Capacity has an estimate value of 0.863, Interaction has an estimate value of 1.06, and Social media variables have an estimate value of 0.857. Thus proving that these variables can be said to have perfect reliability values.